2014
DOI: 10.1371/journal.pone.0099757
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Analyses of Hepatic Differentially Expressed Genes and Blood Biomarkers during the Peripartal Period between Dairy Cows Overfed or Restricted-Fed Energy Prepartum

Abstract: Using published dairy cattle liver transcriptomics dataset along with novel blood biomarkers of liver function, metabolism, and inflammation we have attempted an integrative systems biology approach applying the classical functional enrichment analysis using DAVID, a newly-developed Dynamic Impact Approach (DIA), and an upstream gene network analysis using Ingenuity Pathway Analysis (IPA). Transcriptome data was generated from experiments evaluating the impact of prepartal plane of energy intake [overfed (OF) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 62 publications
5
40
0
5
Order By: Relevance
“…Serum amyloid A is immediately secreted from liver after an inflammatory response (Faty et al, 2012); that is, it is a major APP that binds to toxins and helps clear lipoproteins out of the liver (Malle et al, 1993). Concentration of HP is also increased due to inflammation in the liver (Shahzad et al, 2014). Similarly, HAMP expression is increased shortly after acute inflammatory stimuli (Pigeon et al, 2001;Nicolas et al, 2002), supporting a role for hepcidin as a positive acute-phase response peptide in dairy cattle.…”
Section: Heat Shock and Endoplasmic Reticulum (Er) Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum amyloid A is immediately secreted from liver after an inflammatory response (Faty et al, 2012); that is, it is a major APP that binds to toxins and helps clear lipoproteins out of the liver (Malle et al, 1993). Concentration of HP is also increased due to inflammation in the liver (Shahzad et al, 2014). Similarly, HAMP expression is increased shortly after acute inflammatory stimuli (Pigeon et al, 2001;Nicolas et al, 2002), supporting a role for hepcidin as a positive acute-phase response peptide in dairy cattle.…”
Section: Heat Shock and Endoplasmic Reticulum (Er) Stressmentioning
confidence: 99%
“…For instance, it is well established that the plane of energy nutrition during the dry period can influence the hepatic transcriptome and alter tissue function Shahzad et al, 2014). Because of the well-established decrease in DMI induced by heat stress, it is likely that cows calving in the summer (SU) compared with spring (SP) would experience more pronounced decreases in DMI leading to consequent changes in the hepatic transcriptome.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, microarray analysis from our group revealed a greater overall subclinical inflammatory-like condition in feed-restricted cows compared with overfed cows (Shahzad et al, 2014).…”
Section: Uncover Adaptations During the Transition Period With Omics mentioning
confidence: 68%
“…Data were mined by an integrative systems biology approach applying the newly developed Dynamic Impact Approach (DIA) [24] and an upstream gene network analysis using Ingenuity Pathway Analysis (IPA) [14]. The Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways and Gene Ontology (GO) biological process category database of bovine were used for functional analysis with the DIA.…”
Section: Methodsmentioning
confidence: 99%
“…It has been widely used in the bovine to study the differential gene expression among different treatments or physiological conditions [1416]. Structural genomic studies of domestic animals have indicated that goats are closely related to bovine species [17].…”
Section: Introductionmentioning
confidence: 99%